2018
DOI: 10.1016/j.ajpath.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of AKT1 and PIK3CA in Intraductal Papillomas of the Breast with Special Reference to Cellular Components

Abstract: The pathologic feature of intraductal papillomas is defined as a papillary structure composed of a fibrovascular stromal core lined by luminal epithelial cells and myoepithelial cells. We used droplet digital PCR for the mutational analysis of AKT1 (E17K) and PIK3CA (H1047R, E542K, and E545K) in 60 papillomas. AKT1 and PIK3CA mutations were detected in 12 (20%) and 17 (28%) of the papillomas, respectively. In five tumors harboring mutations, mutational analysis of AKT1 or PIK3CA was performed separately using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
1
9
0
1
Order By: Relevance
“…Our study confirms and extends the findings of previous studies showing that while PIK3CA mutation is common in both benign and atypical pure IDPs 12,13 , they are rare in PC or IDC that arise in the context of IDP. It is unclear whether the lack of PIK3CA mutations in the clonal IDP/carcinomas is by chance due to the limited cases (n = 6) or reflects an intrinsic biological difference in carcinoma arising from an IDP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study confirms and extends the findings of previous studies showing that while PIK3CA mutation is common in both benign and atypical pure IDPs 12,13 , they are rare in PC or IDC that arise in the context of IDP. It is unclear whether the lack of PIK3CA mutations in the clonal IDP/carcinomas is by chance due to the limited cases (n = 6) or reflects an intrinsic biological difference in carcinoma arising from an IDP.…”
Section: Discussionsupporting
confidence: 91%
“…The key limitations of previous IDP studies are the poor resolution of the methods used, that have been performed only on benign IDP, the lack of p63 staining to validate the diagnosis, the very small sample sizes and the absence of CNA data for synchronous cases. In addition, studies concentrating on somatic mutations in PIK3CA and AKT1 in pure IDP and later carcinomas lacked CNA data 12,13 . In the current study, we combine recent improvements in genomic analysis technology with expert pathological review incorporating p63 staining for a cohort consisting of both pure and synchronous cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer (BC) is the malignant neoplasm with the highest prevalence in women (Omarini et al, 2018 ). An extremely high frequency of AKT1(E17K) mutations has been reported in benign papillary tumors of the mammary gland [up to 20–62% (Dunlap et al, 2010 ; Troxell et al, 2010 ; Alves et al, 2018 ; Mishima et al, 2018 )] and is mainly found in BCs with positive estrogen receptor (ER) expression (Stemke-Hale et al, 2008 ; Lauring et al, 2010 ). The E17K mutation appears to be present only in lobular and ductal tissue-type breast tumors (Bleeker et al, 2008 ; Troxell et al, 2010 ), and recent data show a slightly higher rate of liver and lymph node metastasis in patients with E17K mutation (Smyth et al, 2020b ).…”
Section: The Effects Of Akt E17k Mutation Across Various Tumorsmentioning
confidence: 99%
“…3 Histologically, IPs are characterized by the presence of papillary fronds covered by an inner layer of myoepithelial cells and an outer layer of epithelial cells, with or without cellular atypia. 4 There is no convincing epidemiologic or molecular evidence that IPs without atypia are associated with an increased likelihood of a subsequent breast cancer diagnosis, [5][6][7][8] while atypical IPs have been found to be associated with elevated future breast cancer risk. 5,6 The presence of atypia within an IP diagnosed on core biopsy increases the likelihood of finding an associated malignancy on excision, reported in up to 41% of cases, and justifies routine excision of these lesions.…”
mentioning
confidence: 99%